(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
A multi-proxy investigation was carried out on three outcrop sections from the Upper Cretaceous Numanha Formation extended in the Yola Basin of the Northern Benue Trough, Nigeria. The Numanha Formation is a predominantly shale sequence that pre serves the Turonian–Coniacian depositional history of the Atlantic and shallow southern Tethyan seaway. The investigation included palynofacies characterization of the sedimen tary organic matter content of 61 samples collected from three sections, NL10, NL8, and NL4, in addition to analyses for the total organic carbon (TOC) and carbon:nitrogen (C/N) ratios in 44 samples from all of the three studied sections. Palynofacies data confirms an overall marginal marine (estuarine) depositional setting for the Numanha Formation which was strongly impacted by terrestrial and freshwater sources. This is based on the following observations: 1) near-constant presence of marine dinoflagellate cysts and/or benthic planispiral microforaminiferal inner linings, 2) strong terrestrial contribution of transported vascular plant fragments such as opaque, structured, and degraded phyto clasts with fluxes of cuticles at certain intervals, 3) near-constant presence of the fresh water alga Pediastrum which was also recorded in high proportions at certain intervals. TOC content for the majority of the analyzed samples was generally low (<1%) indicating poor organic matter preservation potential which was probably due to high energy and well-oxygenated conditions. C/N ratios were mostly below 20 for the analyzed samples from all sections confirming the inferred marine depositional settings. There were, how ever, two exceptionally high C/N anomalies that were seen in all of the three studied sections, but were especially pronounced in the NL4 section, which were also coupled with elevated TOC content. These are herein interpreted to represent periods of increased terrestrial input, probably as a result of high continental runoff, associated with selective diagenetic consumption of nitrogen by microbial degradation.